Implementación de un sistema de adquisición de datos para la obtención de variables meteorológicas en tiempo real - Guato Barreno, Michael Stalin (2022)
The present technological proposal was made in order to solve the problems of meteorological data recording applied in the locality, with the objective to implement a data acquisition system using a high precision recorder with signal conditioning to obtain meteorological variables, which allowed to collect data of physical variables of advantage sensors of their capacity through a database, initially the system was implemented with respective connection of each sensors to data collector that set input signals, which are physical signals (voltage, resistance and frequency) for recording. Afterwards, a test protocol was carried out where output measurements of each sensor were checked to guarantee operation and communication between sensors and data logger, after this method, it is proceeded to energize the connected equipment to the network and internal power source of data logger with respective protections that guarantee equipment reliability, since being an autonomous instrument, it has the proper protections that safeguard it from surges or unforeseen events on electrical connections, finally, the data recording was carried out through the creation of a database where the behavior of meteorological taken variables during the day can be visualized.